Carbon-carbon bond forming reactions: application of covalently anchored 2,4,6-triallyloxy-1,3,5-triazine (TAT) Pd(II) complex over modified surface of SBA-15 to Heck, Suzuki, Sonogashira and Hiyama cross coupling reactions - Singh, Chandani; Jawade, Kiran; Sharma, Priti; Singh, Anand P.; Kumar, Pradeep (Catalysis Communications, 2015)
A highly active SBA-15-TAT-Pd(II) catalyst was synthesized from organofunctionalized SBA-15 and 2,4,6-triallyloxy-1,3,5-triazine. The catalyst was employed in carrying out Heck, ``copper-free'' Sonogashira, Suzuki and Hiyama cross coupling reactions. Under the optimized conditions the catalyst displays excellent catalytic activity in delivering the desired products in good to excellent yields. The catalytic system exhibited superior activity regarding the time taken for the completion of reaction, isolation, Pd loading (0.62 mmol%) and yields of products as compared to the earlier reported heterogeneous SBA-15 anchored Pd catalysts. The catalyst could be recycled and reused for five times without any appreciable loss of catalytic activity. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Heck; Hiyama; SBA-15-TAT-Pd(II) catalyst; Sonogashira; Suzuki